Climate-induced hydrography change favours small-bodied zooplankton in a coastal ecosystem - K. Mäkinen; I. Vuorinen; J. Hänninen (Springer, 2022)
In the Baltic Sea, the climate change is expected to reduce salinity and increase temperature, and shift mesozooplankton communities towards dominance of small-bodied brackish-water taxa and cause a decline in large-bodied marine taxa. Here, we analyse environmental monitoring data, collected in a coastal area in the northern Baltic Archipelago Sea during May–September, 1967––2013, for trends and relationship between mesozooplankton biomass anomalies, salinity and temperature. During the study period, the surface water temperature increased and salinity decreased. Since the mid-1980s, the community was dominated by small-bodied brackish-water taxa whereas large-bodied calanoid copepods and marine taxa were mostly scarce or absent from the samples. The observed decline of marine taxa was related to the decline in salinity and, to some extent, to the increase of temperature. The brackish-water taxa were, for the most part, positively influenced by the temperature increase, although possibly other direct or indirect factors, not considered in this study, were also influencing the dynamics. This study adds to the knowledge of a possible on-going shift in the food web structure towards smaller-sized species and emphasizes the significance of long-term environmental monitoring in understanding the dynamics in plankton communities